2022
DOI: 10.3390/ma15072513
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Difference in the Pulse Current in the Double Pulsed Gas Metal Arc Welding of Aluminum Alloys

Abstract: In this paper, a double pulse gas metal arc welding (DP-GMAW) for an AA6061-T6 aluminum alloy based on fewer basic welding parameters than the traditional DP-GMAW is proposed. This study compared the difference in pulse base currents (ΔIb) and the difference in the pulse peak currents (ΔIp) by analyzing the electrical signal and morphology properties of welded samples. The results indicated that changing ΔIp caused welding defects or even welding failure easily. The welding stability after changing ΔIb was muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Jin et al [419] compared the difference in pulse base currents (ΔIb) and the difference in the pulse peak currents (ΔIp) for welded joints of 6061-T6 alloys obtained using the double pulse gas metal arc welding DPGMAW. They found that changing ΔIp caused welding defects or even welding failure.…”
Section: Gas Metal Arc Welding Gmawmentioning
confidence: 99%
“…Jin et al [419] compared the difference in pulse base currents (ΔIb) and the difference in the pulse peak currents (ΔIp) for welded joints of 6061-T6 alloys obtained using the double pulse gas metal arc welding DPGMAW. They found that changing ΔIp caused welding defects or even welding failure.…”
Section: Gas Metal Arc Welding Gmawmentioning
confidence: 99%
“…Jin et al [556] compared the difference in pulse base currents (∆Ib) and the difference in pulse peak currents (∆Ip) for the welded joints of 6061-T6 alloys obtained using the double-pulse gas metal arc welding (DPGMAW). They found that changing ∆Ip caused welding defects or even welding failure.…”
Section: Gas Metal Arc Welding (Gmaw)mentioning
confidence: 99%